Kiai as Local Knowledge Authority: The Genealogy of Madurese Ulama’s Role in Shaping Nusantara Islamic Studies - Achmad Muzammil Alfan Nasrullah; Nor Hasan; Zainuddin Syarif; Mohammad Muchlis Solichin; Mohammad Hasan (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The role of the kiai as an epistemic authority remains central in shaping Islamic knowledge within the pesantren tradition, particularly in the context of Nusantara Islam, where religion and local culture interact dynamically. This study aims to analyze how KH. Mohammad Saleh Abdullah constructs, sustains, and disseminates epistemic authority within Pondok Pesantren Mathali’ul Anwar Putri, Sumenep. Employing a qualitative case study design integrated with a genealogical approach, data were collected through in-depth interviews, participant observation, and document analysis over a two-month fieldwork period. The findings reveal four interconnected mechanisms underlying the formation of epistemic authority. First, authority is genealogically constructed through sanad continuity and reinforced by pedagogical discipline that emphasizes foundational learning. Second, kitab kuning functions as an epistemic infrastructure that organizes knowledge transmission through structured methods such as bandongan and sorogan. Third, a hybrid epistemology emerges through the integration of Islamic teachings and local Madurese cultural practices, enabling contextual adaptation without compromising doctrinal principles. Fourth, an alumni network operates as a mechanism for disseminating and reproducing epistemic authority across regions. These findings indicate that epistemic authority in the pesantren context is dynamic, relational, and continuously reproduced through the interaction of tradition, culture, and social networks. This study contributes theoretically by positioning the kiai as an active epistemic agent and introducing hybrid epistemology as a conceptual framework, while practically offering insights into the role of pesantren in fostering contextual and moderate Islamic knowledge.